Method for synthesis of derivative signals systems based on cryptographic discrete sequences of symbols - Горбенко, И.Д.; Замула, А.А.; Семенко, Е.А.; Морозов, В.Л. (Radiotekhnika, 2017)
The requirements have been formulated for choosing systems of complex signals-data carriers for the use in multiuser broadband telecommunication systems (TCS), which have increased requirements for noise immunity, stealth operation and information security data. The conceptual bases of synthesis of a new class of complex cryptographic signals (CS) have been presented. The expediency of the CS application to the protected TCS, including the construction of derivative signal systems to improve the performance of noise immunity, stealth operation and information security data in the protected TCS, have been substantiated.